MINIMISASI BIAYA PRODUKSI KERAJINAN ROTAN PADA MEUBEL SUMBER ROTAN TOHITI DI KELURAHAN TATURA UTARA KECAMATAN PALU SELATAN KOTA PALU - Mohammad Fikri; Arifuddin Lamusa; Sulaeman Sulaeman (Universitas Tadulako, 2019)
This study aimed to determine production cost minimization in order to produce rattan craft furniture for maximization profit in Sumber Rotan Tohiti. This research was conducted in September-December 2015 with the respondent number was five people and Linear Programming used as an analysis tool. Craft products selected included sofa chairs, dining chairs, lounge chairs, recliners and screens. The results of this study showed that the production cost can be minimized to IDR 1,732,768 by managing the utilization of existing resources such as rattan, fryer oil, and labor. The total use of raw materials was 1,755 kg for producing sofa, 1,240 kg for dining chairs, 540 kg for lounge chairs, 156 kg for recliners and 84 kg for screens. The oil used was 1,755 l for sofa, 1,240 l for dining chairs, 540 l for lounge chairs, and 256 l for screens. The labor working days needed was 4.60 for producing sofas, also 4.60 for dining chairs, 4.60 for lounge chairs, 4.40 for reliners and 4.20 for screens.